(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Taguiam JMB, Bayani GU, Pacris Jr. FA, Banadero RR, Baloloy MV. 2022. Assessment of macro-faunal diversity of nipa swamp in Bisagu, Aparri, Cagayan, Philippines. Biodiversitas 23: 1852-1856. Nipa (Nypa fruticans) is one of the most common, widely distributed, and useful trees in the mangrove forest of Southeast Asia. It is being utilized in the production of roof thatching, wine and vinegar, and recent scientific studies have been done for the utilization of nipa sap in the production of bio-ethanol. Moreover, nipa has also contributed ecologically as it acts as a barrier during typhoons and storm surges helps prevent soil erosion along the banks of villages near river areas. The study area is located in barangay Bisagu, Aparri, Cagayan, Philippines where nipa plantation covers 550.51 ha and is utilized by the community. As we all know, mangroves areas as home to aquatic animals thus the study conducted takes on the diversity of macrofaunal species in a nipa-dominated mangrove area. Sampling areas were constructed, the proximal, middle and distal quadrat with 10 m by 10 m dimensions. Species collected in the area yield 11, where 10 is successfully identified and 1 species is not identified. Results showed that macrofaunal species in a nipa-dominated mangrove area show very low diversity. Shannon-wiener diversity index of the community showed a result of only 0.97457 and its equitability at 0.04, which concluded as low species evenness distribution.